2010
DOI: 10.1016/j.cct.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Living Partnerships to Prevent Diabetes (HELP PD): Design and methods

Abstract: Although the Diabetes Prevention Program (DPP) developed a lifestyle weight loss intervention that has been demonstrated to prevent type 2 diabetes in high-risk individuals, it has yet to be widely adopted at the community level. The Healthy Living Partnership to Prevent Diabetes study (HELP PD) was designed to translate the DPP approach for use in community settings as a cost-effective intervention led by Community Health Workers (CHW's) and administered through a Diabetes Care Center (DCC). Approximately 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 45 publications
0
82
0
Order By: Relevance
“…According to a recent meta-analysis of 22 DPP translational studies, these programs have achieved modest success with an average 12-month weight loss of 2.32 kg [13]. The Healthy Living Partnerships to Prevent Diabetes (HELP PD) trial was one of the largest randomized controlled trials to translate the methods of the original DPP [14]. Previously we have shown that the HELP PD intervention was effective in reducing fasting glucose relative to an enhanced usual care condition [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent meta-analysis of 22 DPP translational studies, these programs have achieved modest success with an average 12-month weight loss of 2.32 kg [13]. The Healthy Living Partnerships to Prevent Diabetes (HELP PD) trial was one of the largest randomized controlled trials to translate the methods of the original DPP [14]. Previously we have shown that the HELP PD intervention was effective in reducing fasting glucose relative to an enhanced usual care condition [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…All participants signed informed consent and the Institutional Review Board of Wake Forest University Health Sciences approved the trial. Details regarding the HELP PD trial design, participant recruitment, outcomes, and cost have been published elsewhere [9,10,14,15,[22][23][24]. For the purpose of this evaluation, only data from participants in the lifestyle intervention arm is included.…”
Section: Dpp Lifestyle Balance Interventionmentioning
confidence: 99%
“…It also appears that community health workers may not be optimal providers for a DPP. Additional research is indicated as a preliminary report of a DPP provided by health professionals and community health workers with T2D has demonstrated promising results [37,38]. The effectiveness of community health workers in other behavioral interventions has been variable, depending on their role and the population served.…”
Section: Discussionmentioning
confidence: 99%
“…Absetz, Oldenburg and their colleagues used the Fin-DPS as a benchmark for the Good Ageing in Lahti (GOAL) Region Lifestyle Implementation Trial in Finland [13,14], and the Greater Green Triangle Diabetes Prevention Program (GTT DPP) adapted and tested the GOAL model in Australia [15]. These studies have now been followed by a number of translational studies based on either the Fin-DPS or the US DPP model in other high-income countries (HICs) such as the United States [16][17][18], United Kingdom [19,20], Netherlands [21], Europe [22][23][24], Australia [25] and Japan [10,26]. In the case of the US DPP, the Centers for Disease Control and Prevention (CDC) have now developed a curriculum to ensure adapted programs meet requirements for recognition.…”
Section: Introductionmentioning
confidence: 99%
“…To date, cultural adaptation of T2DM prevention programs has mainly occurred with ethnic groups or indigenous population within HICs and has included settings such as churches [27], health centres and community centres [17,[28][29][30][31][32][33][34][35][36][37]. Efforts to adapt programs and models of delivery for T2DM prevention in lowand middle-income countries (LMICs) have been very limited.…”
Section: Introductionmentioning
confidence: 99%